Click strategies for single-molecule protein fluorescence - Milles, Sigrid; Tyagi, Swati; Banterle, Niccolò; Köhler, Christine; Plass, Tilman; Lemke, Edward A. (Journal of the American Chemical Society, 2012)
Single-molecule methods have matured into central tools for studies in biology. Foerster resonance energy transfer (FRET) techniques, in particular, have been widely applied to study biomolecular structure and dynamics. The major bottleneck for a facile and general application of these studies arises from the need to label biological samples site-specifically with suitable fluorescent dyes. In this work, we present an optimized strategy combining click chemistry and the genetic encoding of unnatural amino acids (UAAs) to overcome this limitation for proteins. We performed a systematic study with a variety of clickable UAAs and explored their potential for high-resolution single-molecule FRET (smFRET). We determined all parameters that are essential for successful single-molecule studies, such as accessibility of the probes, expression yield of proteins, and quantitative labeling. Our multiparameter fluorescence analysis allowed us to gain new insights into the effects and photophysical properties of fluorescent dyes linked to various UAAs for smFRET measurements. This led us to determine that, from the extended tool set that we now present, genetically encoding propargyllysine has major advantages for state-of-the-art measurements compared to other UAAs. Using this optimized system, we present a biocompatible one-step dual-labeling strategy of the regulatory protein RanBP3 with full labeling position freedom. Our technique allowed us then to determine that the region encompassing two FxFG repeat sequences adopts a disordered but collapsed state. RanBP3 serves here as a prototypical protein that, due to its multiple cysteines, size, and partially disordered structure, is not readily accessible to any of the typical structure determination techniques such as smFRET, NMR, and X-ray crystallography.